Clinically aggressive pediatric spinal ependymoma with novel MYC amplification demonstrates molecular and histopathologic similarity to newly described MYCN-amplified spinal ependymomas - Shatara, Margaret; Schieffer, Kathleen M.; Klawinski, Darren; Thomas, Diana L.; Pierson, Christopher R.; Sribnick, Eric A.; Jones, Jeremy; Rodriguez, Diana P.; Deeg, Carol; Hamelberg, Elizabeth; LaHaye, Stephanie; Miller, Katherine E.; et al. (Acta Neuropathologica Communications, 2021)
Primary spinal cord tumors contribute to ≤ 10% of central nervous system tumors in individuals of pediatric or adolescent age. Among intramedullary tumors, spinal ependymomas make up ~ 30% of this rare tumor population. A twelve-year-old male presented with an intradural, extramedullary mass occupying the dorsal spinal canal from C6 through T2. Gross total resection and histopathology revealed a World Health Organization (WHO) grade 2 ependymoma. He recurred eleven months later with extension from C2 through T1-T2. Subtotal resection was achieved followed by focal proton beam irradiation and chemotherapy. Histopathology was consistent with WHO grade 3 ependymoma. Molecular profiling of the primary and recurrent tumors revealed a novel amplification of the MYC (8q24) gene, which was confirmed by fluorescence in situ hybridization studies. Although MYC amplification in spinal ependymoma is exceedingly rare, a newly described classification of spinal ependymoma harboring MYCN (2p24) amplification (SP-MYCN) has been defined by DNA methylation-array based profiling. These individuals typically present with a malignant progression and dismal outcomes, contrary to the universally excellent survival outcomes seen in other spinal ependymomas. DNA methylation array-based classification confidently classified this tumor as SP-MYCN ependymoma. Notably, among the cohort of 52 tumors comprising the SP-MYCN methylation class, none harbor MYC amplification, highlighting the rarity of this genomic amplification in spinal ependymoma. A literature review comparing our individual to reported SP-MYCN tumors (n = 26) revealed similarities in clinical, histopathologic, and molecular features. Thus, we provide evidence from a single case to support the inclusion of MYC amplified spinal ependymoma within the molecular subgroup of SP-MYCN.